Traffic State Index (TSI) in amazonian waters: Marajó bay and Guajará bay (Research, Society and Development, 2020)
Monitoring water quality is of fundamental importance, because through it we can reduce problems related to pollution and contamination of water bodies. One can cite eutrophication as one of the problems related to water quality, this being a phenomenon that consists of the proliferation of algae in water bodies. Research aimed at studying water quality indexes is opportune to help prevent major problems, related to public health, human well-being and even drinking. In this sense, this work aimed to obtain the Trophic State Index (EIT) in Amazonian waters and to compare the results of total phosphorus and / or chlorophyll a according to CONAMA 357/2005. The calculations were performed according to the methodology of Lamparelli (2004), being an adaptation for tropical environments of the index adopted by Carlson (1977). It is noticed that the lake Bologna and the Bay of Guajará, obtained values ​​of “Supereutrófico” and variation of “Ultraliogotrófico” to “Supereutrófico” respectively for TSI, being possible to associate the use and occupation of the soil near the sampling points and the interference of the studied water resource. The Pará river and the Maratauíra river had a low risk of eutrophication, with a predominance of the “ultraoligotrophic” state, indicating that the study areas had a low degree of trophy. Total phosphorus values ​​above the limit established by CONAMA Resolution 357/2005 were obtained in the works carried out in Guajará Bay and Lake Bologna for class 2 freshwater. In the port area of ​​Barcarena and Maratauíra River, they presented low concentrations of total phosphorus.